2010
DOI: 10.1136/bcr.10.2010.3387
|View full text |Cite
|
Sign up to set email alerts
|

Central serous chorioretinopathy secondary to childbirth

Abstract: SummaryA previously healthy 37-year-old woman presented with decreased vision in the right eye, noted suddenly during childbirth. Fundus examination revealed elevation at the right macula, and optical coherence tomography confirmed central serous chorioretinopathy in the right eye. No intervention was undertaken, and the symptoms and clinical findings resolved spontaneously over 2 months. BACKGROUND

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…Consistent with previous studies, this study showed that pregnancy-associated CSC developed mostly in the third trimester and usually recovered spontaneously around the time of delivery with good final visual acuity [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Consistent with previous studies, this study showed that pregnancy-associated CSC developed mostly in the third trimester and usually recovered spontaneously around the time of delivery with good final visual acuity [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16].…”
Section: Discussionsupporting
confidence: 89%
“…Acute central serous chorioretinopathy (CSC), a common macular disease, usually presents with a well-circumscribed serous retinal detachment at the posterior pole on clinical examination and one or more leakage points at the level of the retinal pigment epithelium (RPE) on fluorescein angiography (FA) [1]. Pregnancy-associated CSC typically develops in the third trimester and is characterized by the onset of subretinal hyperreflective fibrin, spontaneous, and complete resolution of subretinal fluid around the time of delivery and good final visual acuity [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Cases have been reported in Caucasian, black, Native American, Hispanic, and Middle Eastern women [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hirji et al 12 have described CSC as a finding more commonly associated with a complicated pregnancy (eg, eclampsia), but most cases reported in the literature deal with uncomplicated pregnancies.…”
Section: Discussionmentioning
confidence: 99%